Protocol for an online randomised controlled trial to evaluate the clinical and cost-effectiveness of a peer-supported self-management intervention for relatives of people with psychosis or bipolar disorder: Relatives Education And Coping Toolkit (REACT). Issue 7 (18th July 2017) - Lobban, Fiona; Robinson, Heather; Appelbe, Duncan; Barraclough, Johanna; Bedson, Emma; Collinge, Lizzie; Dodd, Susanna; Flowers, Sue; Honary, Mahsa; Johnson, Sonia; Mateus, Ceu; Mezes, Barbara; et al.
Abstract : Introduction: Despite clinical guidelines recommendations, many relatives of people with psychosis or bipolar disorder do not currently receive the support they need. Online information and support may offer a solution. Methods and analysis: This single-blind, parallel, online randomised controlled trial will determine clinical and cost-effectiveness of the Relatives Education And Coping Toolkit (REACT) (including an online resource directory (RD)), compared with RD only, for relatives of people with psychosis or bipolar disorder. Both groups continue to receive treatment as usual. Independent, web-based variable, block, individual randomisation will be used across 666 relatives. Primary outcome is distress at 24 weeks (measured by General Health Questionnaire; GHQ-28) compared between groups using analysis of covariance, adjusting for baseline score. Secondary clinical outcomes are carer well-being and support. Cost-effectiveness analysis will determine cost of a significant unit change (three-point reduction) in the GHQ-28. Costs include offering and supporting the intervention in the REACT arm, relevant healthcare care costs including health professional contacts, medications prescribed and time off (or ability to) work for the relative. Cost utility analysis will be calculated as the marginal cost of changes in quality-adjusted life years, based on EuroQol. We will explore relatives' beliefs, perceived coping and amount of REACT toolkit use as possible outcome mediators. We have embedded two methodological substudies in the protocol to determine the relative effectiveness of a low-value (£10) versus higher value (£20) incentive, and an unconditional versus conditional incentive, on improving follow-up rates. Ethics and dissemination: The trial has ethical approval from Lancaster National Research Ethics Service (NRES)Committee (15/NW/0732) and is overseen by an independent Data Monitoring and Ethics Committee and Trial Steering Committee. Protocol version 1.5 was approved on 9 January 2017. All updates to protocols are uploaded to the National Institute for Health Research (NIHR) Journals Library. A full statistical analysis plan is available at https://figshare.com/account/home #/projects/19975. Publications will be in peer-reviewed journals (open access wherever possible). Requests for access to the data at the end of the study will be reviewed and granted where appropriate by the Trial Management Group. Trial registration number: ISRCTN72019945, pre-results.